PERLINDUNGAN KONSUMEN TERHADAP BEREDARNYA MAKANAN KADALUARSA DI KOTA KUPANG - Wohon , Ernesta Uba; Hironima Letik , Miriam Claudia; Recon Dopo Due , Ferdinandus Mario; Wage , Guido Tobhi; Limu , Kristian Umbu (Gapenas Publisher, 2025)
The circulation of expired food in Indonesia is a serious problem that threatens the health and safety of consumers. This study examines the aspect of consumer protection against the circulation of food products that have passed the safe consumption time limit. The research method uses a normative juridical approach with an analysis of related laws and regulations, especially Law Number 8 of 1999 concerning Consumer Protection and Law Number 18 of 2012 concerning Food. The results show that although there is a legal framework that regulates consumer protection, its implementation is still weak in preventing the circulation of expired food. The main causative factors include weak supervision from the relevant authorities, sanctions that do not provide a deterrent effect, and low consumer awareness in checking expiration dates. The impact is not only economic losses, but also health risks that can lead to food poisoning to death. Consumer protection efforts require a comprehensive approach through strengthening the supervisory system, increasing administrative and criminal sanctions, consumer education, and coordination between related institutions. The research recommendations include the need for regulatory revisions to provide stricter sanctions, the establishment of an integrated reporting system, and ongoing education programs to improve consumer literacy in choosing safe food products.